Anesthetic Approach to Placenta Previa with Associated Bladder Rupture: A Case Report - Putra, Made Bagus Cahya Maha; IGAG Utara Hartawan; Dewa Ayu Mas Shintya Dewi (Udayana University and Indonesian Society of Anesthesiologists (PERDATIN), 2025)
This case report outlines the anesthetic management of total placenta previa with high-risk features of placenta accreta spectrum (PAS) complicated by bladder rupture, representing a rare but clinically significant form of invasive placentation. A 29-year-old G2P1001 at 35+3 weeks’ gestation presented with recurrent antepartum bleeding and ultrasonographic features consistent with PAS, including grade III lacunae, bridging vessels, severe myometrial thinning, and a Placenta Accreta Indeks (PAI) score of 6. Spinal anesthesia was initiated for delivery, followed by a controlled conversion to general anesthesia to facilitate hysterectomy, two-layer bladder repair, ureteral reconstruction, and Double-J stent placement. Hemodynamic stability was maintaned using tranexamic acid, colloid co-loading, invasive arterial monitoring, and norepinephrine titration. An estimated blood loss of 2,300 mL was managed with targeted transfusion, resulting in favourable maternal recovery and neonatal outcomes (Apgar 7 and 9). This case underscores the importance of early PAS recognition, structured anesthetic planning, and coordinated multidisciplinary care, supporting the benefit of a staged neuraxial-to-general anesthesia strategy in complex PAS with urologic involvement.